1961
DOI: 10.1073/pnas.47.10.1530
|View full text |Cite
|
Sign up to set email alerts
|

The Inactivation of Trypsin by Ultraviolet Light, I. The Correlation of Inactivation With the Disruption of Constituent Cystine

Abstract: common with preparations of thyrotropin and a-intermedin, increased the oxygen consumption of isolated leporine adipose tissue incubated in vitro."5 Summary.-Two metabolically active substances designated peptides I and II have been purified from a crude extract of porcine anterior pituitary glands. Electrophoresis on starch gel served as a guide during fractionation, which was accomplished using an anion-exchange resin and Sephadex G-50. Peptide I of molecular weight near 5,000 was homogeneous upon electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1962
1962
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(6 citation statements)
references
References 23 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…The photosensitivity of protein-bound cystine residues has been shown to depend on their microenvironment (Augenstein and Ghiron 1961;Dose and Rajewsky 1962;Augenstein and Riley 1964;Dose 1964Dose , 1967Fiore and Dose 1965;Grist et al 1965;Risi et al 1967;Koudelka and Augenstein 1968). This correlates with the observation by Petersen et al (1999) that cystine residues (cysteines involved in disulphide bridges) have a clear preference for aromatic residues as spatial neighbors.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…The photosensitivity of protein-bound cystine residues has been shown to depend on their microenvironment (Augenstein and Ghiron 1961;Dose and Rajewsky 1962;Augenstein and Riley 1964;Dose 1964Dose , 1967Fiore and Dose 1965;Grist et al 1965;Risi et al 1967;Koudelka and Augenstein 1968). This correlates with the observation by Petersen et al (1999) that cystine residues (cysteines involved in disulphide bridges) have a clear preference for aromatic residues as spatial neighbors.…”
mentioning
confidence: 63%
“…It was also found that the effective destruction of cystine, tryptophan, tyrosine, and phenylalanine occurs on UV irradiation of proteins (Kazutomo 1955; Augenstine and Ghiron 1961; McLaren and Luse 1961; Hideko and Kazutomo 1963; Dose 1964; Vladimirov and Roshchupkin 1964; Cooper and Davidson 1965; Fujimoro 1966; Piras and Vallee 1966; Vladimirov et al 1970). The photosensitivity of protein‐bound cystine residues has been shown to depend on their microenvironment (Augenstein and Ghiron 1961; Dose and Rajewsky 1962; Augenstein and Riley 1964; Dose 1964, 1967; Fiore and Dose 1965; Grist et al 1965; Risi et al 1967; Koudelka and Augenstein 1968). This correlates with the observation by Petersen et al (1999) that cystine residues (cysteines involved in disulphide bridges) have a clear preference for aromatic residues as spatial neighbors.…”
mentioning
confidence: 99%
“…Photoinduced oxidative damage can occur directly upon absorption of UV radiation by aromatic residues or indirectly through the generation of reactive oxygen species (ROS) upon absorption of visible light by photosensitizers (Sgarbossa et al, 2003). Less well documented is the sensitivity of disulfide bonds to UV damage (Augenstine, 1962;Augenstine and Ghiron, 1961;Grist et al, 1965). The exact mechanism by which disulfide bonds are destroyed remains unclear; however, recent evidence suggests that aromatic residues close to disulfide bonds are important (Neves-Petersen et al, 2002).…”
Section: Iðhklþmentioning
confidence: 99%
“…Auganstine et al· (114,129), have studied the ultraviolet and ionising It has been found that a general relationship exists between molecular weight and quantum yields for ultraviolet inactivation (123,124).…”
Section: Possible Methods Of Enhancemen T Of Photodynam Ic Actionmentioning
confidence: 99%